Isolation, characterization, and LC MS/MS determination of anti-obesity components from pine needles of Cedrus deodara (Roxb.) G. Don - Wang, Xin; Li, Bin; Liu, Dongyan; Guo, Yuer; Zhang, Jiaxu; Li, Wanyu; Peng, Tengteng; Ma, Quhuan; Shi, Xiaofeng (Frontiers in Nutrition, 2024)
Objective This study aimed to isolate and analyze the components in Cedar pine needles (needle leaves of Cedrus deodara (Roxb.) G. Don) that have a anti-obisity effect, guided by animal experiments. Methods The extract of Cedar pine needles was separated into four fractions of different polarities by a macroporous resin column. The fraction that retained the anti-obesity activity was evaluated based on the results of animal experiments. Monomeric compounds were isolated from the active fraction using a preparative liquid chromatography system combined with a glucose gel column and structurally characterized come with it. The content of the separated components was determined by UPLC-QQQ-MS/MS. Results The water-washed fraction retained the anti-obesity activity of Cedar pine needles better. A total of 16 compounds were separated from this fraction, and the contents of 14 of them were determined in Cedar pine needles. Conclusion Nine components including p-Hydroxybenzyl alcohol, Chlorogenic acid，Vanillic acid，Syringic acid，P-Coumaric acid，Sinapic acid，Benzoic acid， Phenylacetic acid， Sallcylic acid were characterized and determined for the first time in Cedar pine needles. The components with anti-obesity activity in the pine needles of the Cedrus may mainly come from phenolic acids.